Differences and Diagnosis of Mammary Tumors in Mammals: A Scientific Review - Huda Hameed Kadhim Alabbody (American Journal of Biomedicine and Pharmacy, 2025)
The aim of review is to discuss the incident of tumors in the mammary glands of three type female mammals (canine bovine and human) and to know the susceptibility of these species to take tumors. Usually, the diagnosis of mammary tumors is based on the case history, clinical findings, and ultrasound examination. Mammary gland lesions diagnosis is confirmed by staining the tissue sections and reading the cancerous or precancerous cellular changes. It is also preferable to use immunohistochemistry tests with tumor markers, which can be diagnostic, therapeutic and informative of tumor behavior at the same time such as BRCA1 and Ki67. The review showed that female dogs are more susceptible to mammary tumors which are often classified into adeno, lipo and carcinoma. Women have also been found to have different types such as ductal carcinoma in situ, lobular carcinoma in situ, or fibroadenomas. In cows, studies find masses in the mammary glands so rarely. The conclusion is that carnivores like female dogs are more susceptible to mammary tumors than women, while herbivores such as cows are the most resistant. Therefore, the review recommends further studies to focus on the variation among animal species in order to reduce the incidence of mammary tumors in mammals, especially humans and canines.